Isolating the Unique Effects of the Unified Protocol Treatment Modules Using Single Case Experimental Design. (March 2017) - Sauer-Zavala, Shannon; Cassiello-Robbins, Clair; Conklin, Laren R.; Bullis, Jacqueline R.; Thompson-Hollands, Johanna; Kennedy, Katherine A.
The Unified Protocol (UP) for the Transdiagnostic Treatment of Emotional Disorders is a cognitive-behavioral intervention designed to treat the range of anxiety, depressive, and related disorders. Thus far, the UP treatment modules have only been studied when they are delivered in their entirety and presented in a standard sequence. To personalize the presentation of the UP modules for a given patient's presentation (e.g., providing the modules in a varied order, dropping irrelevant modules), it is first necessary to establish that each module leads to change in the skill it is designed to promote, and that these changes can occur in the absence of the other modules. Using a multiple baseline design in accordance with the single-case reporting guidelines in behavioral interventions (SCRIBE), eight patients with heterogeneous emotional disorders were randomly assigned to a 1- or 3-week baseline assessment phase followed by four sessions of one of four UP modules (psychoeducation, emotional awareness, cognitive flexibility, and countering emotional behaviors). Results provide preliminary support for the notion that each UP module under study leads to change in its associated skill in the absence of the other modules (five of eight patients demonstrated reliable change in the module-specific skill). In addition, exploratory analyses suggest that the emotion awareness training and cognitive flexibility modules appeared to exhibit change specific to their associated skills, psychoeducation, and countering emotional behaviors demonstrated somewhat more broad-based change across skills.